Actinobacillus capsulatus peritonitis and chyloabdomen in a Warmblood gelding. (8th December 2017) - Cullimore, A. M.; Lester, G. D.; Stephens, N.
Summary: Primary peritonitis in horses attributable to Actinobacillus equuli has been reported in Australia, New Zealand and North America. Published reports describe a rapid response to treatment with appropriate antimicrobial and supportive treatment and an excellent prognosis for survival. To our knowledge, this is the first reported case of Actinobacillus capsulatus in the horse. The case was complicated by the development of an idiopathic chylous abdominal effusion. The report highlights the importance of molecular methods in the correct identification of bacterial species. Prognosis for horses diagnosed with Actinobacillus peritonitis may be guarded given the atypical response to appropriate antimicrobial treatment in this case.